PRODUCTION OF ALTERNATIVE ROAD BITUMEN AND QUALITY ASSESSMENT (Scientific journal of the Fergana State University, 2023)
The article describes in detail the process of obtaining alternative road bitumen with high adhesion using a thermooxidation experimental device based on gossypol resin, oil sludge and used diethanolamine waste. The results of "passive" adhesion of alternative road bitumen to mineral materials in the preparation of A-type asphalt mixture and the parameters of the limit angle of wetting were obtained and compared with road bitumen obtained from standard oil. Then, the best indicator was given by the adhesion of the alternative bitumen on "passive" connection of 96%, and the limiting angle of wetting was 74 degrees. The obtained alternative road bitumen provides an opportunity to produce high-quality asphalt mixture according to the specifications.